Aligned MHD Magnetic Nanofluid Flow Past a Static Wedge - Rijal Ilias, Mohd; Afiqah Rawi, Noraihan; Hidayah Mohd Zaki, Noor; Shafie, Sharidan (International Journal of Engineering and Technology, 2018)
The problem of steady aligned MHD magnetic nanofluid flow past a static wedge is studied in this paper. The present aligned magnetic field along with constant temperature at the surface is considered. The governing partial differential equations, subject to boundary conditions are transformed into ordinary differential equations using similarity transformations. The transformed equations are then solved numerically by Keller-box method. To check the validity of the present method, numerical results for dimensionless local skin friction coefficient and rate of heat transfer are compared with results of available literature as special cases and revealed in good agreement. The influence of pertinent parameters on velocity, temperature profiles, as well as wall shear stress and heat transfer rate is displayed in graphical form and discussed. It is found that fluid velocity increases with the increase of inclined angle, magnetic parameter and thermal buoyancy parameters while decreasing for increasing in nanoparticle volume fraction.Â It is also noticed that magnetic parameter influences fluid velocity and temperature significantly.Â Â Â